Curated Database Construction for sMMO-Containing Methanotrophs - Zuser, Christina (Jihočeská univerzita, 2023)
The significance of methane as an energy source is discussed, specifically focusing on understanding the ecology and metabolism of methanotrophs belonging to the families Methylococcaceae, Methylocystaceae, and Beijerinckiaceae. It includes applying bioinformatic tools, primer design, and a comparative analysis of metagenome-assembled genomes using the NCBI database, shedding light on phyla representation discrepancies. The study contributes to understanding methanotrophic diversity.
Curated Database Construction for sMMO-Containing Methanotrophs
Keywords: Methanotrophs; sMMO (soluble methane monooxygenase); Methylococcaceae; Methylocystaceae; Beijerinckiaceae; Primer design; Metagenome-Assembled Genomes (MAGs); Phylogenetic analysis; Methanotrophs; sMMO (soluble methane monooxygenase); Methylococcaceae; Methylocystaceae; Beijerinckiaceae; Primer design; Metagenome-Assembled Genomes (MAGs); Phylogenetic analysis